Exploring The Effects of Environmental, Social and Governance (ESG) on Banking Performance: A Case Study of Far East Asia - Adhiguna Wijaya Indrasuci; Rofikoh Rokhim (Indonesian Journal of Economics and Management, 2023)
Extensive research has focused on the connection between ESG and banking performance. However, a literature gap exists in the study of the influence of ESG disclosures on the banking and financial services sector, particularly in Far East Asia and ASEAN countries compared to Europe and North America. This study addresses this gap by employing data panel regression to investigate how environmental, social, and governance (ESG) factors affect bank performance in these regions. We analyze the correlation between ESG performance and various measures of bank performance: return on assets (ROA), return on equity (ROE), Tobin's Q, and Stock Return. Our findings reveal that stronger ESG performance in banks tends to have a negative impact on financial, operational and market performance. This research contributes to the existing literature on the relationship between ESG factors and banking performance and offers valuable insights for policymakers, investors, and banking practitioners in Far East Asia.